The points would be (9,9) , (0,-6) , (6,-9)
I hope this helps !
It asked to choose all the points so ( B, C, E )
Answer:
You buy six newspaper ads & eighteen social media ads.
Step-by-step explanation:
First, we change ads into variables to be more easier to calculate :
Let newspaper = x
Let social media = y
Second, make this variables into an equation, given that you purchase a total of 24 ads :
x + y = 24 (first equation)
Next, given that x = $18.50 & y = $26.50 & spent a total of $588 so you can make another equation :
18.50x + 26.50y = 588 (second equation)
Now, solve this simultaneous equation using elimination or substitution (depends on you) :
substitution =>
x + y = 24 ----------(1)
18.50x + 26.50y = 588 ---------(2)
(1)=> y = 24 - x ------(3)
(3)=>(2) 18.5x + 26.5(24-x) = 588
18.5x + 636 - 26.5x = 588
-8x = -48
x = 6
sub x=6 into(3)
(3)=> y = 24 - 6
= 18
newspaper = x
= 6
social media = y
= 18
Answer:
a) b = 8, c = 13
b) The equation of graph B is y = -x² + 3
Step-by-step explanation:
* Let us talk about the transformation
- If the function f(x) reflected across the x-axis, then the new function g(x) = - f(x)
- If the function f(x) reflected across the y-axis, then the new function g(x) = f(-x)
- If the function f(x) translated horizontally to the right by h units, then the new function g(x) = f(x - h)
- If the function f(x) translated horizontally to the left by h units, then the new function g(x) = f(x + h)
In the given question
∵ y = x² - 3
∵ The graph is translated 4 units to the left
→ That means substitute x by x + 4 as 4th rule above
∴ y = (x + 4)² - 3
→ Solve the bracket to put it in the form of y = ax² + bx + c
∵ (x + 4)² = (x + 4)(x + 4) = (x)(x) + (x)(4) + (4)(x) + (4)(4)
∴ (x + 4)² = x² + 4x + 4x + 16
→ Add the like terms
∴ (x + 4)² = x² + 8x + 16
→ Substitute it in the y above
∴ y = x² + 8x + 16 - 3
→ Add the like terms
∴ y = x² + 8x + 13
∴ b = 8 and c = 13
a) b = 8, c = 13
∵ The graph A is reflected in the x-axis
→ That means y will change to -y as 1st rule above
∴ -y = (x² - 3)
→ Multiply both sides by -1 to make y positive
∴ y = -(x² - 3)
→ Multiply the bracket by the negative sign
∴ y = -x² + 3
b) The equation of graph B is y = -x² + 3
Answer:
d = r * t
r = 50 mph
this will be very easy.
d = r * t
r = 50 mph
t = 5 hours
d = 250 miles
In five hours at a constant speed of 50 miles per hour, you would have traveled 250 miles.t = 5 hours
d = 250 miles
In five hours at a constant speed of 50 miles per hour, you would have traveled 250 miles.